2016
DOI: 10.1037/cdp0000091
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, psychological adjustment, and parenting styles of Chinese immigrant mothers in the United States.

Abstract: Objectives This study examined whether acculturation to American culture, maintenance of Chinese culture, and their interaction predicted Chinese immigrant parents’ psychological adjustment and parenting styles. We hypothesized that American orientation would be associated with more positive psychological well-being and fewer depressive symptoms in immigrant mothers, which in turn would be associated with more authoritative parenting and less authoritarian parenting. The examination of the roles of Chinese ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 108 publications
10
53
1
Order By: Relevance
“…Therefore, how much mothers acculturate towards the mainstream American culture may be more likely to differentiate first-generation immigrant mothers than the degree to which they maintain their heritage Chinese culture. This finding is also consistent with the larger body of research that has found stronger implications of immigrants’ orientation toward the mainstream culture for their psychological adjustment and parenting practices than their orientation towards their heritage culture (e.g., Hwang & Ting, 2008; Yu, Cheah, & Calvin, 2016). Interestingly, however, maternal enculturation was directly associated with lower levels of child internalizing and externalizing problems at W2.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, how much mothers acculturate towards the mainstream American culture may be more likely to differentiate first-generation immigrant mothers than the degree to which they maintain their heritage Chinese culture. This finding is also consistent with the larger body of research that has found stronger implications of immigrants’ orientation toward the mainstream culture for their psychological adjustment and parenting practices than their orientation towards their heritage culture (e.g., Hwang & Ting, 2008; Yu, Cheah, & Calvin, 2016). Interestingly, however, maternal enculturation was directly associated with lower levels of child internalizing and externalizing problems at W2.…”
Section: Discussionsupporting
confidence: 88%
“…Immigrant parents from collectivist backgrounds may struggle with upholding their traditional parenting beliefs and customs and adapting practices from the culture of their host country (Kim, Ahn, & Lam, 2009; Yaman, Mesman, van IJzendoorn, Bakermans‐Kranenburg, & Linting, 2010). These findings are consistent with research that indicates that acculturation can be a stressful process for parents (Miao, Costigan, & MacDonald, 2018; Yu, Cheah, & Calvin, 2016), and call for additional support and resources to help these parents cope with acculturation‐related stressors. Furthermore, complex individual and community‐level factors may contribute to a higher risk of PPD in immigrant women, including a lack of social support and financial burdens.…”
Section: Background/rationalesupporting
confidence: 89%
“…However, during the preschool developmental period, mothers begin to interact with the larger mainstream American community (i.e. school, children's peers and their parents), and experience a heightened and self-conscious period of parental socialization (Yu, Cheah, & Calvin, 2016).…”
Section: Introductionmentioning
confidence: 99%